Understanding the HERA Phase I receiver system with simulations and its impact on the detectability of the EoR delay power spectrum. Issue 1 (22nd October 2020) - Fagnoni, Nicolas; de Lera Acedo, Eloy; DeBoer, David R; Abdurashidova, Zara; Aguirre, James E; Alexander, Paul; Ali, Zaki S; Balfour, Yanga; Beardsley, Adam P; Bernardi, Gianni; Billings, Tashalee S; Bowman, Judd D; et al.
ABSTRACT: The detection of the Epoch of Reionization (EoR) delay power spectrum using a 'foreground avoidance method' highly depends on the instrument chromaticity. The systematic effects induced by the radio telescope spread the foreground signal in the delay domain, which contaminates the EoR window theoretically observable. Applied to the Hydrogen Epoch of Reionization Array (HERA), this paper combines detailed electromagnetic and electrical simulations in order to model the chromatic effects of the instrument, and quantify its frequency and time responses. In particular, the effects of the analogue receiver, transmission cables, and mutual coupling are included. These simulations are able to accurately predict the intensity of the reflections occurring in the 150-m cable which links the antenna to the backend. They also show that electromagnetic waves can propagate from one dish to another one through large sections of the array due to mutual coupling. The simulated system time response is attenuated by a factor 10 4 after a characteristic delay which depends on the size of the array and on the antenna position. Ultimately, the system response is attenuated by a factor 10 5 after 1400 ns because of the reflections in the cable, which corresponds to characterizable k ∥ -modes above 0.7 h Mpc^-1 at 150 MHz. Thus, this new study shows that the detection of the EoR signal with HERA Phase I will be more challenging than expected. On the other hand, it improves our understanding of the telescope, which is essential to mitigate the instrument chromaticity.